Pengaruh Social Media Marketing dan Brand Image Terhadap Kepuasan Pelanggan Cititrans Bandung - Yayu Rahayu; Adi Suparwo; Famati Gulo (Bulletin of Management and Business, 2022)
This study aims to determine the effect of social media marketing and brand image on customer satisfaction Cititrans Bandung. This research uses descriptive and verification research methods with a quantitative approach. The object of this research is Cititrans Bandung service users with a sample of 100 people. The sampling technique used in this study is a non- probability sampling method with a purposive sampling technique. Statistical analysis of the data used in this study is multiple linear regression analysis using IBM SPSS statistics 25. The results of the study found that social media marketing, brand image and customer satisfaction at Cititrans Bandung were good. There is a significant influence between social media marketing and brand image simultaneously on customer satisfaction at Cititrans Bandung. There is a significant influence between social media marketing partially on customer satisfaction at Cititrans Bandung. There is a significant influence between brand image partially on customer satisfaction at Cititrans Bandung. This research is different from other researchers because there are no other researchers who specifically examine social media marketing and brand image on customer satisfaction at Cititrans Bandung. of the social media marketing variable has a greater value and influence than the brand image variable.